Employment Of foreign labours in the Malaysian construction industry: Contractor's perspective - Hasan, Sharina Farihah; Mohd Nordin, Siti hajar (2011)
Labour is one of the main resources required by contractors before any construction processes can be initiated. It is a well known fact that foreign labour dominated the workforce in the Malaysian construction industry. This paper reports on a preliminary study on foreign labour employment from contractor's perspective. The objective of the study is to identify and understand the critical reasons behind foreign labour employment by contractors. The methodology involves review of literatures and questionnaire survey. The paper concludes that contractor is in favor of foreign labour employment due to the various benefits they offer and that mainly to overcome the shortage of local workforce in the industry.